Epidemiological Characteristics of Human Rabies at Infectious Disease Hospital, Dhaka - Haque, Md Shahidul; Yeasmin, Tahmina; Islam, Md Manirul (Bangladesh Journal of Child Health, 2012)
Objective: To describe the epidemiological characteristics of human rabies at IDH, Dhaka in 2006. Methods: Analysis of the records of rabies cases admitted into the Infectious Disease Hospital, Dhaka in 2006 (Jan-Dec). Results: Of total 170 rabies cases, 116(68.2%) cases were admitted to IDH from Dhaka division and rest 44(31.8%) cases came from other areas of Bangladesh. Majority (59.5%) of the victims were within 15 years of age. Male (67.1%) gender & rural people (89.4%) constituted the main bulk of the cases. 86.5% cases had WHO category III exposure. Majority cases had incubation period between 16-90 days (82.9%). Hydrophobia which is the main pathognomonic feature of human rabies, was present in cent percent cases. Principal biting animals was dog (92.94%). Others animals were cat(5.3%),jackal (0.6%), mongoose (1.2%). Most cases (143/170=84.1%) were not vaccinated. 99% cases did not take wound care. Among 27 cases who received vaccines, only 6 cases (22.2%) received TCV inadequately and remaining 21(77.8%) received NTV. None of 170 cases were treated with RIG. Conclusion: Rabies is a major health problem in Bangladesh. The data indicates that the epidemiological characteristics of the disease are not much different from other studies and have not changed much over the decades. Hence, there are need to educate the community and health workers about the importance of immediate and adequate post-exposure treatment, to start effective control programme for dog and to make availability of TCV as well as RIG. DOI: http://dx.doi.org/10.3329/bjch.v35i3.10521 Bangladesh J Child Health 2011; Vol 35 (3): 102-107